2021
DOI: 10.1371/journal.pone.0261005
|View full text |Cite
|
Sign up to set email alerts
|

Women’s post-abortion contraceptive use: Are predictors the same for immediate and future uptake of contraception? Evidence from Ghana

Abstract: This study seeks to identify the socio-demographic, reproductive, partner-related, and facility-level characteristics associated with women’s immediate and subsequent use of post-abortion contraception in Ghana. Secondary data from the 2017 Ghana Maternal Health Survey were utilized in this study. The weighted data comprised 1,880 women who had ever had an abortion within the five years preceding the survey. Binary logistic regression analyses were performed to examine the associations between the predictor an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Post-abortion contraception utilization may be important for women who do not want to become pregnant. 18 20 However, different studies revealed that it is underutilized public health intervention in Ethiopia and the study area in particular. 21 23 Thus, the main aim of this study was to determine the level of PACU and associated factors among reproductive age group women who received abortion services in Bahir Dar City, North West Ethiopia.…”
Section: Introductionmentioning
confidence: 98%
“…Post-abortion contraception utilization may be important for women who do not want to become pregnant. 18 20 However, different studies revealed that it is underutilized public health intervention in Ethiopia and the study area in particular. 21 23 Thus, the main aim of this study was to determine the level of PACU and associated factors among reproductive age group women who received abortion services in Bahir Dar City, North West Ethiopia.…”
Section: Introductionmentioning
confidence: 98%
“…There have been suggestions that socio-demographic characteristics such as age, ethnicity/racial differences, marital status, socio-economic status, educational status, and religious belief can play a key role in the pattern of uptake of contraception among women [ 5 - 8 ]. It was found that black women were less likely to use contraceptives as compared to whites in the United States of America [ 6 ]. Furthermore, greater acceptance of post-abortion contraceptives occurred among women who received post-abortion contraceptive counseling and services at health centers or maternity homes as compared to hospitals [ 7 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, greater acceptance of post-abortion contraceptives occurred among women who received post-abortion contraceptive counseling and services at health centers or maternity homes as compared to hospitals [ 7 , 9 , 10 ]. However, while some studies reported that young women are more receptive to post-abortion contraceptives, older women were more interested in post-abortion family planning in other settings [ 6 - 8 ]. Partner´s support and participation during the abortion process may influence the women´s acceptance and use of post-abortion contraception [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation